Ku posthumanistycznej wspólnocie. Eko-logika, czyli myślenie domem - Markiewicz, Miłosz (Studia Europaea Gnesnensia, 2018)
The article is an attempt to review the ecological discourse in the light of posthuman philosophy. The main concept addressed by the author is the Anthropocene; the author observes that the Anthropocene functions as an ambivalent philosophical metaphor, which underlies contemporary ecological discourse. The author advances a new concept which, in his opinion, could replace ecology. The concept is called eco-logics, and may be defined as ‘thinking through home’.